Transformasi Ideologis Muhammadiyah di Abad Kedua: Sintesis antara Tradisi, Modernitas, dan Spirit Islam Berkemajuan: Analisis Literatur - Wahyudi Mutalib; Mohammad Nahrawi; Ahmad Mujahidin; Heri Rifhan Halili (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study examines the ideological transformation of Muhammadiyah in its second century by highlighting the synthesis between tradition, modernity, and the spirit of Progressive Islam (Islam Berkemajuan). As a modernist Islamic movement established in the early 20th century, Muhammadiyah continues to negotiate its ideological identity within the context of global social, political, and epistemological changes. The purpose of this research is to reveal how Muhammadiyah constructs an ideological reconstruction that is able to integrate the normative values of Islam with modern rationality and a commitment to universal humanity. This study employs a library research method with a content analysis approach using primary sources such as the Matan Keyakinan dan Cita-Cita Hidup Muhammadiyah (MKCH), the Pedoman Hidup Islami Warga Muhammadiyah (PHIWM), and contemporary Muhammadiyah thinkers’ works. The analysis shows that Muhammadiyah’s ideology has shifted from theological purification toward an integrative ideological formation, in which Progressive Islam serves as an adaptive paradigm to address the challenges of modernity. Theoretically, this research contributes to the development of modern Islamic epistemology by emphasizing the importance of synthesizing revelation, reason, and social reality. Practically, the findings recommend revitalizing Muhammadiyah’s role as a global agent of change rooted in Islamic values while remaining open to scientific advancement and universal humanistic principles. Thus, the ideological transformation of Muhammadiyah in its second century becomes a paradigmatic model of progressive Islam relevant to modern civilization.